Blogging and what it means to be Malaysian: the push and pull cultures - Mohamed, Shafizan (KUALA LUMPUR INFRASTRUCTURE UNIVERSITY COLLEGE (KLIUC), 2011)
Freedom of speech and expression is often contested in Malaysia. Because of strict laws, it becomes hard; and to some extent; dangerous for Malaysians to participate in open political expressions and discussions. The availability of new media technologies is challenging this forced custom. Blogs particularly enable everyday Malaysians to become interactive social activists and political actors. However, the relationship between blogging and democratic participation is not necessarily causal. Therefore, this paper contextualizes the historical, sociological and cultural precedence to the Malaysian blogging experience by delineating the different influences that might contribute to how Malaysians make sense and make do with this new found freedom. By applying James Lull’s (2006) conceptualization of the ‘pull and push culture’, I propose that the Malaysian blogging experience is influenced by the interconnection of three main conditions which include the bloggers’ perception and experience of: 1) citizenship, 2) media use and 3) the individualization of new media.